Grain Characteristics, Moisture, and Specific Peptides Produced by Ustilaginoidea virens Contribute to False Smut Disease in Rice (Oryza sativa L.) - Robinson C. Jose; Thangjam Kanchal; Bengyella Louis; Narayan C. Talukdar; Devasish Chowdhury (Biomolecules, 2023)
The fungus Ustilaginoidea virens, the causative agent of false smut in rice (Oryza sativa L.), is responsible for one of the severe grain diseases that lead to significant losses worldwide. In this research, microscopic and proteomic analyses were performed by comparing U. virens infected and non-infected grains of the susceptible and resistant rice varieties to provide insights into the molecular and ultrastructural factors involved in false smut formation. Prominent differentially expressed peptide bands and spots were detected due to false smut formation as revealed by sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and two-dimensional gel electrophoresis (2-DE) SDS-PAGE profiles and were identified using liquid chromatography-mass spectrometry (LC-MS/MS). The proteins identified from the resistant grains were involved in diverse biological processes such as cell redox homeostasis, energy, stress tolerance, enzymatic activities, and metabolic pathways. It was found that U. virens produces diverse degrading enzymes such as β-1, 3-endoglucanase, subtilisin-like protease, putative nuclease S1, transaldolase, putative palmitoyl-protein thioesterase, adenosine kinase, and DNase 1 that could discretely alter the host morphophysiology resulting in false smut. The fungus also produced superoxide dismutase, small secreted proteins, and peroxidases during the smut formation. This study revealed that the dimension of rice grain spikes, their elemental composition, moisture content, and the specific peptides produced by the grains and the fungi U. virens play a vital role in the formation of false smut.